Dissipation of Energy in Tissues of Berry Fruit of Selected Plants Species under Cyclic Load Conditions (Agricultural Engineering, 2017)
Dissipation hypothesis of energy under cyclic loads conditions was used to characterize the behavior of berry fruit. The possibility of dissipation of energy as a result of plastic deformations (Dawidenkow hypothesis) or visco-elastic deformations (Voigt hypothesis) was considered. Tests of hysteresis of whole fruit squeezed among two rigid plates for various levels of load and with various speeds of deformation of samples for two directions of load application were conducted for verification of the usefulness of both hypotheses. The strength tests were preceded by the test of hysteresis, the mass and the geometry of fruit were determined additionally as well as conventional density and moisture was counted. A mutual relation of average values of the coefficients of elasticity EC was accepted as the measure of dissipation of energy as a result of changes in the angle of inclination of the curve in the springy return phase. Voigt hypothesis was con- firmed as useful within the range of small speeds of deformation and lack of usefulness of the Dawidenkow hypothesis was proved.